2010
DOI: 10.3141/2142-20
|View full text |Cite
|
Sign up to set email alerts
|

American Road Map for Research for Nanotechnology-Based Concrete Materials

Abstract: The mechanical behavior of concrete materials depends to a large extent on structural elements and phenomena that are effective on micro- and nanoscales. The nanomodification of concrete materials has the potential to open up new uses and classes of concrete materials, with wideranging implications for the concrete transportation infrastructure. The development of nanotechnology-based concrete materials will require a multidisciplinary approach, consisting of teams of civil engineers, chemists, physicists, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Portland cement is a commonly used binder material to form the heterogeneous mortar or concrete matrix, and the durability of concrete structures and components in service environments is of great interest to practicing engineers and researchers. In this context, many approaches have been investigated to improve the durability properties of concrete, with a focus on modification of the binder. As a promising emerging technology in construction, nanotechnology has been applied in the production of concrete and proven to enhance the mechanical properties (e.g., compressive strength, ductility, impact resistance) and reduce shrinkage and permeability, all of which contribute to extension of the concrete’s service life. …”
Section: Introductionmentioning
confidence: 99%
“…Portland cement is a commonly used binder material to form the heterogeneous mortar or concrete matrix, and the durability of concrete structures and components in service environments is of great interest to practicing engineers and researchers. In this context, many approaches have been investigated to improve the durability properties of concrete, with a focus on modification of the binder. As a promising emerging technology in construction, nanotechnology has been applied in the production of concrete and proven to enhance the mechanical properties (e.g., compressive strength, ductility, impact resistance) and reduce shrinkage and permeability, all of which contribute to extension of the concrete’s service life. …”
Section: Introductionmentioning
confidence: 99%
“…Environmental and economic benefits of nanoclays, such as their excellent compatibility with water-based systems reducing the need for harmful solvents and volatile organic compounds, and their renewability, have recently created sizable interest in nanoclay-based composites. Research showed that incorporating nanoclays into the geopolymer paste increased the water volume used, consequently lowering the setting time and improving solidity of the paste [226][227][228][229], which resulted improvements in selfcompaction, ductility, durability, weight reduction, air quality, resistance to chloride penetration, reduction in water and oxygen permeability, lessening in shrinkage, increase in the mechanical strength, and resistance to chemical solvents of the concrete [88,230]. Optimization in the amount of nanoclays used in the mix determines the best performance; adding a higher percentage may diminish the performance, which is caused by the agglomeration of the nanoparticles [231].…”
Section: Sustainability and Environmental Considerationsmentioning
confidence: 99%
“…The properties of concrete are governed by the varying characteristics of its constituents; which gives it a great advantage to enjoy the benefits of nanotechnology for the modification of the atomic and molecular matters of its various constituents in order to develop an enhanced concrete. Scholarly research reports on the adoption of nanotechnology in concrete and building constructions, have focused on the nanostructure, the modification of the atomic structure of concrete and cement-based materials and their fracture mechanism [3,[13][14][15][16][17][18][19][20][21]. Nanotechnology improves the bulk property of concrete, helps to obtain thinner final products, faster setting time and lowered levels of environmental attack.…”
Section: Nano-concretementioning
confidence: 99%